THE USE OF MATCHING GAME TO SUPPORT VOCABULARY BUILDING FOR LEARNING SPECIFIC TERMS IN LOCAL FOLKLORE - Muslimin, .; Sutapa Y, Y .Gatot; Wardah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:This research aimed to support student’s vocabulary building by using matching game for learning specific term in local folklore to the seventh-grade students in academic year 2015/2016. This research was conducted through A-Pre-Experimental design to solve the problems that happened in the class, which was students’ lack of vocabulary related to term in local folklore. The sample of this research was class VII B students which consisted of 34 persons. The researcher used measurement technique to collect the data, while the tool of data collecting was an objective test which consisted of 30 matching test items. The research findings show that matching game improves the students’ vocabulary mastery.In this research, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It indicates that matching Game enhanced the vocabulary mastery of the seventh-grade students in academic year 2015/2016. In conclusion, matching game is effective to support the students’ learning of specific term in local folklore.Keywords: Vocabulary, Specific Term, Matching Game